Environmental regulations and inward FDI in China: Fresh evidence from the asymmetric autoregressive distributed lag approach. (2nd September 2020) - Ullah, Assad; Zhao, Xinshun; Abdul Kamal, Muhammad; Zheng, Jiajia
Abstract: The relationship between environmental regulations and foreign direct investment (FDI) has garnered extensive attention, particularly in the context of China. The puzzle of whether environmental regulations deter or lure FDI has not resolved to the satisfaction of the curious mind. This research endeavor is to answer the question by exploring the asymmetric association between environmental regulations and FDI in China; utilizing a novel nonlinear autoregressive distributed lag (NARDL) approach. Our main results affirm that environmental regulations and FDI move together in the long‐run, and there is dependable evidence of asymmetry. We notice that FDI inflows react differently in response to positive and negative shocks of environmental regulations both in the long‐ and short‐run. The findings of our study corroborate both the "Pollution Haven" and the "Pollution Halo" hypotheses in China. The Chinese policymakers should strike a balance between environmental stringency and leniency pertaining to inbound FDI for sustainable economic growth—concurrently keeping environmental issues at bay.